(untitled) (Asian Journal of Pharmaceutics (AJP), 2022)
Objective: The study proposed to explore the anti-adipogenic activity of 3-Hydroxyflavone on 3T3-L1 pre-adipocyte differentiation. Method: 3T3-L1 pre-adipocytes were differentiated into adipocytes in the presence of (3, 3 × 102 and 3 × 104 ng/well) 3-Hydroxyflavone for 6 days, the untreated 3T3-L1 pre-adipocytes served as control. After differentiation, the adipocytes were subjected to Oil Red O staining and the m RNA expression of leptin, peroxisome proliferator activated receptor (PPARγ), and the Sterol regulatory element-binding transcription factor 1 (SREBP-1) were studied. Results: A round-shaped adipocytes were appeared in the cultured medium on the 6th day of the study period. The untreated adipocytes showed intense accumulation of the red dye; however, a dose-dependent reversal of red dye accumulation was seen in the adipocytes on 3-Hydroxyflavone exposure. The m RNA expressions of leptin, PPAR γ and SREBP in the untreated adipocytes were significantly up regulated. However, on 3-Hydroxyflavone treatment, the m RNA expressions of leptin, PPAR γ and SREBP in the adipocytes were down regulated in a dose-dependent manner. The high dose (3 × 104 ng per well) of 3-Hydroxyflavone appreciably reduced the oil accumulation and also significantly down regulated the expression of leptin, PPAR γ and SREBP in the adipocytes. Conclusion: The 3-Hydroxyflavone displayed the anti-adipogenic activity in the adipocytes by reducing the oil accumulation and also by down regulating the m RNA expression of leptin, PPAR γ and SREBP, which are need for the adipogensis.